Advertisement Remove all ads

Solve the Following Equation: A'B'X' + B'X - A'X - 1 = 0 - Mathematics

Sum

Solve the following equation:  a2b2x2 + b2x - a2x - 1 = 0  

Advertisement Remove all ads

Solution

a2b2x2 + b2x - a2x - 1 = 0

b2 x(a2 x + 1)- 1(a2 x + 1) = 0  

(a2 x + 1)(b2 x- 1) = 0  

x = `-1/"a"^2`  , x = `1/"b"^2`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Frank ICSE Class 10 Mathematics Part 2
Chapter 6 Quadratic Equations
Exercise 6.1 | Q 36
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×